Antimicrobial capabilities of non-spermicidal concentrations of tea tree (Melaleuca alternifolia) and rosemary (Rosmarinus officinalis) essential oils on the liquid phase of refrigerated swine seminal doses. (December 2019) - Elmi, Alberto; Prosperi, Alice; Zannoni, Augusta; Bertocchi, Martina; Scorpio, Diana G.; Forni, Monica; Foni, Emanuela; Bacci, Maria Laura; Ventrella, Domenico
Abstract: Antimicrobial resistance is increasing within the porcine industry with consequential high impact on human health, leading to a need for new antimicrobials. Lately, the scientific community has turned its interest towards natural compounds, and different essential oils have been tested on spermatozoa for preliminary assessment of toxicity before considering them as good substitutes for standard antibiotics. The aim of the present work was to investigate the potential antimicrobial effect of Melaleuca alternifolia and Rosmarinus officinalis essential oils, already evaluated for toxicity, on swine artificial insemination doses deprived of spermatozoa and stored at 16 °C for 5 days. This was accomplished by setting up an in vitro model with a standardized quantity of E. coli . Essential oils, previously chemo-characterized by means of gas chromatography, were tested at 0.2 and 0.4 mg/ml. Analyses, performed at 24 and 120 h, included optical density evaluation, bacterial DNA quantification by qPCR, and colony count. The results demonstrate that both Melaleuca alternifolia and Rosmarinus officinalis essential oils, at a concentration of 0.4 mg/ml, are capable of delivering similar effects to ampicillin, used as control, on the experimental samples. At the lower concentration, M. alternifolia essential oil seemed more effective when compared to R. officinalis . Overall, these findings strengthen the hypothesis of the potential use of phyto-complexes as antimicrobial agents for reproductive biotechnologies. Highlights: Essential oils may act as antimicrobial agents in seminal doses. 0.4 mg/ml of Tea tree or Rosemary essential oils deliver similar effects to ampicillin. At lower concentration Tea tree oils seems more effective than Rosemary. The in vitro model set up for the study proved to be reliable and reproducible.